Utilization of Plastic Bottle Waste as Material for Making Sustainable Cement-Less Aesthetic Paving Blocks - Karisma, Dwifi Aprillia; Nursandah, Fauzie; Rahmawaty, Fitry (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Plastic is a key ingredient in many products around the world, but its existence has caused serious problems due to the buildup of waste it produces. The construction industry is one of the sectors that can play a role in the utilization of plastic waste. One of them is in the production of paving blocks. This study aims to combine aesthetic aspects and environmental attractiveness in paving blocks without sustainable cement.  An experimental method was chosen to develop an alternative to making sustainable paving blocks without the use of cement. Variations used to start from 20% PET: 80% aggregate, 25% PET: 75% aggregate, 30% PET: 70% aggregate, 35% PET: 65% aggregate, 40% PET: 60% aggregate. The aggregates used are sand and stone ash. Physical and mechanical qualities of paving blocks, such as compressive strength, absorption is carried out to determine the quality of paving blocks. The aesthetic aspect is also in focus by carrying out the concept of "glow in the dark". The results of physical and mechanical quality evaluation show that this paving block has adequate performance. The ratio of 20% PET and 80% sand reached paving category C with a compressive strength of 19.65 MPa, while the mixture with a ratio of 20% PET and 80% stone ash reached paving category B with a compressive strength of 24.20 MPa. This paving can be applied in the use of parks, pedestrian to parking lots. This suggests that the use of PET in the mixture can achieve sufficient strength in the paving industry. However, higher water absorption in mixtures with a higher percentage of PET needs to be taken into consideration. In addition, morphological and structural analysis reveals the presence of pores in the paving block that can affect the overall strength. These pores are caused by uneven melting of PET plastic during the manufacturing process. Based on the LCC evaluation, a higher economic value was obtained, but the resulting environmental impact made the product worthy of being one of the solutions to reduce plastic waste.